Address by YAB Tun Dr Ismail Al-Haj,Deputy Prime Minister Of Malaysia to Members Of German Association for foreign policy at Adenauerallee 133,Bon,on Thursday 9th December 1971 at 6.00 pm. - Al-Haj, Ismail (1971)

(untitled)
The Challenge In Southeast Asia. Ladies and Gentlemen, I am deeply honoured to have been invited to address this distinguished gathering in Bonn, the capital of a powerful and friendly country which, no less than mine, is preoccupied with the supreme and urgent tasks of strengthening cooperation and reducing tensions between nations.